Isolated Square‐Planar Copper Center in Boron Imidazolate Nanocages for Photocatalytic Reduction of CO2 to CO - Zhang, Hai‐Xia; Hong, Qin‐Long; Li, Jing; Wang, Fei; Huang, Xinsong; Chen, Shumei; Tu, Wenguang; Yu, Dingshan; Xu, Rong; Zhou, Tianhua; Zhang, Jian (Angewandte Chemie International Edition, 2019)
Photocatalytic reduction of CO2 to value‐added fuel has been considered to be a promising strategy to reduce global warming and shortage of energy. Rational design and synthesis of catalysts to maximumly expose the active sites is the key to activate CO2 molecules and determine the reaction selectivity. Herein, we synthesize a well‐defined copper‐based boron imidazolate cage (BIF‐29) with six exposed mononuclear copper centers for the photocatalytic reduction of CO2. Theoretical calculations show a single Cu site including weak coordinated water delivers a new state in the conduction band near the Fermi level and stabilizes the *COOH intermediate. Steady‐state and time‐resolved fluorescence spectra show these Cu sites promote the separation of electron–hole pairs and electron transfer. As a result, the cage achieves solar‐driven reduction of CO2 to CO with an evolution rate of 3334 μmol g−1 h−1 and a high selectivity of 82.6 %. The cat on the cage: A copper‐based boron imidazolate cage with isolated, coordinatively unsaturated single copper atom active sites was found to be as an excellent co‐catalyst for highly efficient and selective solar‐driven CO2 reduction to CO.